2012
DOI: 10.1103/physrevb.86.104306
|View full text |Cite
|
Sign up to set email alerts
|

Application of the wavelet transform to nanoscale thermal transport

Abstract: The continuous wavelet transform is employed to analyze the dynamics and time-dependent energy distribution of phonon wave-packet propagation and scattering in molecular dynamics simulations. The equations of the one-dimensional continuous wavelet transform are presented and then discretized for implementation. Practical aspects and limitations of the transform are discussed, with attention to its application in the analysis of molecular dynamics simulations. The transform is demonstrated using three examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…For clarity, L i and L * are redrawn in figure 6(d) as a function of charge carrier density. We found that L ϕ , L i and L * are in line with previous reports for SLG [14,15]. The value of L i (=150 ∼ 210 nm) of the SLG is much larger than that of the artificially stacked double-layer graphene.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For clarity, L i and L * are redrawn in figure 6(d) as a function of charge carrier density. We found that L ϕ , L i and L * are in line with previous reports for SLG [14,15]. The value of L i (=150 ∼ 210 nm) of the SLG is much larger than that of the artificially stacked double-layer graphene.…”
Section: Resultssupporting
confidence: 92%
“…However, a relatively low-cost and feasible approach is chemical vapor deposition (CVD) on metal (Cu, Ni) substrate for largescale growth of graphene [12]. Although a few experiments have been performed on CVDgrown or epitaxially grown graphene [13][14][15], the WL effect is a mesoscopic quantum transport phenomenon that is still a fascinating result from the phase coherence of charge carriers. The interference of electron waves that are scattered by disorder and form closed trajectories leads to an enhancement in resistivity, resulting in the localization of electrons [7][8][9][16][17][18][19].…”
mentioning
confidence: 99%
“…Such an extension of the Fourier transform is common in signal processing but has found so far little echo to study the dynamics of wavepackets [39]. We show in Fig.…”
mentioning
confidence: 91%
“…Such simulations allow for direct observations of transport and are discussed in Chapter [Shiomi]. In an unsteady simulation, spatial and temporal temperature variations may exist, allowing for observation of processes such as the propagation of a phonon wave packet [57,58].…”
Section: Formulationmentioning
confidence: 99%
“…As such, the creation of a phonon wave packet requires a fine resolution of the Brillouin zone. For example, in the non-equilibrium unsteady wave packet technique for studying how phonons interact with interfaces, simulation cells thousands of unit cells long are required to form sufficient localized wave packets [57,58].…”
Section: How To Think About Phonons In An Equilibrium Molecular Dynammentioning
confidence: 99%